Galanthus plicatus Bieb. у Донецькому ботанічному саду НАН України - Pavlova, М.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
Biomorphologic peculiarities of Galanthus plicatus Bieb. have studied at the Donbass: morphology of vegetative and generative organs, seasonal develop ment rhythm, capacity to vegetative and seed propagation. The estimate of introduction successfulness is given and the ways of using this species in greenery planting have been determined.